Sophocarpine Attenuates LPS-Induced Liver Injury and Improves Survival of Mice through Suppressing Oxidative Stress, Inflammation, and Apoptosis - Zhengyu Jiang; Yan Meng; Lulong Bo; Changli Wang; Jinjun Bian; Xiaoming Deng (Hindawi Limited, 2018)
Septic liver injury/failure that is mainly characterized by oxidative stress, inflammation, and apoptosis led to a great part of terminal liver pathology with limited effective intervention. Here, we used a lipopolysaccharide (LPS) stimulation model to simulate the septic liver injury and investigated the effect of sophocarpine on LPS-stimulated mice with endotoxemia. We found that sophocarpine increases the survival rate of mice and attenuates the LPS-induced liver injury, which is indicated by pathology and serum liver enzymes. Further research found that sophocarpine ameliorated hepatic oxidative stress indicators (H2O2, O2∙−, and NO) and enhanced the expression of antioxidant molecules such as superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH). In addition, sophocarpine also attenuated regional and systematic inflammation and further reduced apoptosis of hepatocytes. Mechanistic evidence was also investigated in the present study as sophocarpine inhibited hepatic expression of the CYP2E/Nrf2 pathway during oxidative stress, inactivated p38/JNK cascade and NF-κB pathway, and, meanwhile, suppressed PI3K/AKT signaling that reduced apoptosis. Conclusively, the present study unveiled the protective role of sophocarpine in LPS-stimulated oxidative reaction, inflammation, and apoptosis by suppressing the CYP2E/Nrf2/ROS as well as PI3K/AKT pathways, suggesting its promising role in attenuating inflammation and liver injury of septic endotoxemia.